Travel Health Knowledge and Perception of Foreign Backpackers Traveling in Bali - Ni Made Dian Kurniasari; Desak Nym. Widyanthini; I Ketut Hari Mulyawan; I Md. Ady Wirawan (Faculty of Public Health, Sriwijaya University, 2021)
International travel to a country has potentially carry health risks for travelers, including backpackers. To date, little is known about Travel Health knowledge and perception among foreign backpackers traveling to Bali. This study aimed to explore the level of knowledge and perception, as well as health information that backpackers need in their destination, Bali. This was a descriptive cross-sectional study, conducted from December 2017 to January 2018 in Bali. This study involved 133 backpackers, taken by convenience sampling technique. Data were collected using a self-administered questionnaire and were analysed descriptively. The results showed that backpackers' knowledge was inadequate, especially to common diseases or health problems that occurred to travelers in Bali. There were 94.74% have low knowledge about rabies, 48.87% have less knowledge about methanol poisoning and 58.65% have low knowledge about diarrhoea. A total of 69.18% backpackers have a perception that they were not prone to being exposed to diseases and health problems in Bali and 36.84% were not aware that they had to seek health information before traveling to Bali. Almost all stated that they needed complete, destination-specific health information. It is necessary to increase backpackers' knowledge and awareness regarding Travel Health at the destination. The development of integrated health promotion media about travel health in Bali, in form of web-based or application-based is one of the strategies to consider.